Aktivitas Hepatoprotektif Ekstrak Etanol Daun Kucing-kucingan Acalypha indica L.) pada Tikus Putih (Rattus Novergicus) yang Diinduksi Parasetamol - T Armansyah TR; Amalia Sutriana; Dwinna Aliza; Henni Vanda; erdiansyah rahmi (Fakultas Peternakan Universitas Jambi, 2010)
The research has been conducted to determine hepatoprotective effect of ethanolic extract of Acalypha indica L. leaves on rats (Rattus novergicus) induced with paracetamol. The study was performed following a completely randomized design, using 45 male rats (Rattus novergicus) divided into 5 groups. Rats in group 1 (K1) were given CMC 1 % for 7 days and followed by aquadest administration 8 hours post given CMC on day 7. Group 2 was given CMC 1 % for 7 days and treated with paracetamol at dose 2,5 g/kg BW 8 hours post given CMC on day 7. Groups 3 (K3), 4 (K4), and 5 (K5) were pretreated with ethanolic extract of Acalypha indica L. leaves at the dose of 50, 100, and 200 mg/kg BW for 7 days respectively, followed by paracetamol administration at the dose of 2.5 g/kg BW in the next 8 hours on day 7. Paracetamol hepatotoxicity and extracts activity were measured based on SGPT and SGOT activity level on day 0, 8 hours after last administration of extract on day 7, and 24 hours post paracetamol administration. Data were analyzed using one way ANOVA. The result showed that the administration of ethanolic extract of Acalypha indica leaves at the dose of 50, 100, and 200 mg/kg BW was significantly reduced SGPT and SGOT level (P<0,05) in rats that were induced with paracetamol. Based on the results of SGPT and SGOT serum activity, it can be concluded that ethanolic extract of Acalypha indica L. potential as hepatoprotective agent.